Development of a Sustainability Awareness Tool for High School Biology Students - Latifah, Suci Siti; Widodo, Ari; Kaniawati, Ida; Sriyati, Siti (Journal Of Biology Education Research (JBER), 2024)
In the context of classroom-based learning, the majority of students tend to acquire cognitive knowledge. It is essential for students to not only acquire cognitive knowledge but also develop awareness of sustainability as a result of teaching and learning activities. The purpose of this study was to develop an instrument to measure sustainability awareness among high school students. Developing an instrument of sustainability awareness for students is important to measure and encourage their understanding and actions in preserving the environment sustainably. The instrument developed consists of three subdimensions: economy, society, and environment. This instrument assesses awareness of the concept of sustainable development and practices, attitudes, and moral values ​​for sustainability at the individual level. This study used the Rasch modeling analysis technique. The instrument is a closed questionnaire containing 21 items using a 4-point Likert scale. The results of the Rasch modeling showed that the overall Cronbach's alpha reliability coefficient was in the "good" category, while the item reliability coefficient was in the "very good" category. However, the student reliability coefficient was in the "weak" category. The results of the instrument validity test showed four invalid items. These items showed ZSTD and Pt Mean Corr values ​​that did not meet the established criteria. However, the existence of invalid instrument items and weak student reliability coefficients did not affect the overall quality of the instrument. Therefore, it can be concluded that the developed instrument is considered appropriate for measuring the sustainability awareness profile of students.